Development of a Web-Based Information System for Food Availability and Production at the Makassar City Food Security Agency - Hijir Ismail; Dyah Darma Andayani; A.Baso Kaswar (Program Studi Teknik Komputer, 2025)
This research is motivated by issues related to the limitations of information and data management in the Field of Food Availability and Production at the Makassar City Food Security Agency. To address these issues, the research focuses on developing a web-based information system aimed at improving the efficiency of data and information management in this sector. Additionally, the study seeks to evaluate the system’s performance by applying the ISO/IEC 25010 standard. The research adopts a research and development (R&D) approach, utilizing the Agile development model, which consists of six stages: requirements, design, development, testing, review, and implementation. The system is tested based on the ISO/IEC 25010 standard, assessing eight key aspects: functionality suitability, usability, reliability, compatibility, performance efficiency, maintainability, portability, and security. The testing outcomes confirm that the developed system aligns with the ISO/IEC 25010 standard. Consequently, the web-based information system for the Field of Food Availability and Production at the Makassar City Food Security Agency demonstrated feasibility for implementation.